The role of agriculture in the circular economy (perspectives for legislation and policy) - Goździewicz-Biechońska, Justyna (Wydawnictwo Naukowe UAM, 2016)
Among concepts developed within socio-environmental sustainability debates, the circular economy framework has recently received increasing attention. It is particularly interesting from the legal perspective, because of the current actions of the European Commission fostering EU transition to the circular economy, with recently adopted a Circular Economy Package. The aim of the article is to explore areas of theoretical and practical application of the circular economy concept to address contemporary challenges in agri-food system and identify its potential opportunities in order to enhance and optimise sustainability within the European economy by using this CE tool. It is pointed out that circular economy constitutes a useful term allowing to conceptualise the path for development of agriculture and whole economy as well, to face contemporary challenges and target environmental issues. The agricultural sector has a significant potential in the framework of circular economy, which has also been confirmed (however indirectly) in the EU’s strategy on circular economy.

Tra le concezioni elaborate nell’ambito di una discussione riguardante lo sviluppo socio-ambientale sostenibile, la formula di un’economia a circuito chiuso (circular economy, CE) gode di un crescente interesse. Essa è particolarmente interessante dal punto di vista giuridico viste le misure adottate attualmente dalla Commissione europea per promuovere la transizione dell’Europa verso un’economia circolare, con in prima linea il c.d. pacchetto sull’economia a circuito chiuso adottato di recente. L’obiettivo dell’articolo è di esaminare i campi di applicazione teoretica e pratica della concezione dell’economia circolare con la finalità di risolvere i problemi dei moderni sistemi agro-alimentari e di identificare potenziali opportunità al fine di rafforzare e ottimizzare lo sviluppo sostenibile dell’economia europea con gli strumenti derivanti da questo concetto. Nello studio si indica che essa è utile per concettualizzare il percorso di sviluppo dell’agricoltura e di tutta l’economia, ma anche per affrontare attuali sfide e obiettivi ambientali. Il settore agricolo possiede notevoli potenzialità nell’ambito dell’economia circolare, il che è stato anche confermato (benché indirettamente) nella strategia dell’Ue.
Il ruolo dell’agricoltura nella economia circolare (prospettiva giuridica e politica)